Multi-time Scale Dispatch Approach for an AC/DC Hybrid Distribution System Considering the Response Uncertainty of Flexible Loads - Zhao, Dongmei; Wang, Haoxiang; Tao, Ran (Electric power systems research, 2021)
•“New Generation Dispatching and Control System” is being developed in China.•Demand response was involved in many aspects of the power system operations.•Response uncertainties of flexible loads of the power system need to be considered.•Establish the price-based demand response model and incentive-based demand response model, respectively.•A multi-time scale dispatch model considering the response uncertainty of flexible loads for an AC/DC hybrid distribution system is proposed, which involves a day-ahead, intra-day, and real-time dispatch scheme. This paper examines the response uncertainty of flexible loads in the multi-time scale operation of an AC/DC hybrid distribution system. The price-based demand response (PBDR) model is established based on the principle of consumer psychology and the law of actual response uncertainty. The incentive mechanism of the incentive-based demand response (IBDR) model is designed considering the error of actual response capacity. Then, fuzzy chance-constrained programming is adopted to handle the response uncertainty of flexible loads. A multi-time scale dispatch model considering the response uncertainty of flexible loads for an AC/DC hybrid distribution system is proposed, which involves a day-ahead, intra-day, and real-time dispatch scheme. Mixed integer second-order cone programming (MISOCP) is utilized to solve the established multi-time scale dispatch model. Case studies illustrate the effectiveness of the proposed model, by considering the response uncertainty of flexible loads and the coordinated optimization on multiple time scales, peak shaving and valley filling can be realized and the dispatching cost of network can be reduced.